2011
DOI: 10.3341/kjo.2011.25.1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Volume of Tumor Mass and Visual Field Defect in Patients with Pituitary Macroadenoma

Abstract: PurposeWe used the Swedish interactive threshold algorithms (SITA) standard strategy of Humphrey perimetry, to analyze the pattern of visual field (VF) defects and evaluate the quantitative correlation between the tumor volume and severity of VF defects in patients with pituitary macroadenoma.MethodsWe reviewed 50 patients with pituitary macroadenoma who received VF test and 11 patients were excluded. VF analysis was performed with Humphrey perimeter using the SITA standard strategy. The tumor volume was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 21 publications
3
30
1
Order By: Relevance
“…Similar findings were seen by Meenakshi Y. D et al 5 Bitemporal hemianopia was the predominant field defect in a similar study by Jung Pil Lee et al 7 Bitemporal hemianopia could not be demonstrated to be most common field defect in our study. The probable reason might be that some patients were already on medical treatment for the tumour that might have contributed to regression of the defect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar findings were seen by Meenakshi Y. D et al 5 Bitemporal hemianopia was the predominant field defect in a similar study by Jung Pil Lee et al 7 Bitemporal hemianopia could not be demonstrated to be most common field defect in our study. The probable reason might be that some patients were already on medical treatment for the tumour that might have contributed to regression of the defect.…”
Section: Discussionsupporting
confidence: 92%
“…PSD shows the pattern of a localised abnormality. 7 Both of the parameters are expressed numerically, so those are useful to quantify the VF defects more accurately.MD and PSD values obtained from the automated perimetry chart showed significant difference when compared to controls. MD was worse than that in the control group (-8.18 ± 8.65 dB vs. -2.0 ± 1.8 dB) and PSD values were higher than controls (5.76 ± 4.8 dB vs. 1.9 ± 1.0 dB).…”
Section: Discussionmentioning
confidence: 99%
“…AP being the standard of practise for VF assessment is an automated testing which uses computer algorithm (25). AP is independent of the examiner and conducted by computer in a standard manner making it ideal to follow up patients VF with this method.…”
Section: Introductionmentioning
confidence: 99%
“…This value is crucial to see the changes of VF defect over time and signifies overall abnormality of a single VF. One of the factor that was found to be correlated with preoperative severity of the VF deficit is tumor volume (25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation